2020
DOI: 10.17721/1728_2748.2020.80.10-15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of compound DM509 on kidney fibrosis in the conditions of the experimental model

Abstract: Kidney fibrosis is a key event in the development of chronic kidney disease, leading to end-stage renal failure. Unfortunately, there are now few drugs capable of preventing fibrosis in the kidneys, which is accompanied by the progression of chronic kidney disease in the terminal stage of renal failure. The results show the effectiveness of the use of a new dual-acting agent DM509 in the prevention of renal fibrosis using a model of unilateral obstruction of the ureter in mice. DM509 is both a farnesoid X-rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Considering the complexity of CKD pathogenesis involving different cell types and changes of multiple signal pathways, multi-target drugs (MTD) emerge as a useful tool; for example, soluble epoxide hydrolase (SHE)-based PTUPB (with cyclo-oxygenase 2 (COX2) inhibitor), PB394 (with PPARγ agonist), and DM509 (with farnesoid X receptor agonist) to alleviate fibrosis, inflammatory response, and oxidative stress from CKD related to DM, hypertension, hyperlipidemia, or other etiologies [ 166 , 167 , 168 ].…”
Section: Specific Issues Of Ckdmentioning
confidence: 99%
“…Considering the complexity of CKD pathogenesis involving different cell types and changes of multiple signal pathways, multi-target drugs (MTD) emerge as a useful tool; for example, soluble epoxide hydrolase (SHE)-based PTUPB (with cyclo-oxygenase 2 (COX2) inhibitor), PB394 (with PPARγ agonist), and DM509 (with farnesoid X receptor agonist) to alleviate fibrosis, inflammatory response, and oxidative stress from CKD related to DM, hypertension, hyperlipidemia, or other etiologies [ 166 , 167 , 168 ].…”
Section: Specific Issues Of Ckdmentioning
confidence: 99%
“…The promise of FXR activation to treat cardiovascular and kidney fibrosis is dampened by unwanted increases in cholesterol levels in humans (Mudaliar et al, 2013;Neuschwander-Tetri et al, 2015). Dual modulating drugs with FXR agonism have avoided this problem and are demonstrating promising actions to combat kidney and cardiovascular diseases (Miyazaki-Anzai et al, 2010;Stavniichuk et al, 2020).…”
Section: Ppars and Fxr In Hypertensionmentioning
confidence: 99%
“…55 DM509 had anti-inflammatory actions with reductions in TGF-β, tumor necrosis factor- (TNF), interleukin-1 (IL-1), and interleukin-6 (IL-6) levels in the UUO mice. 55 With this highly promising in vivo profile, DM509 stands as a potential lead candidate for preclinical evaluation to combat organ fibrosis and kidney diseases.…”
Section: Dm509mentioning
confidence: 99%
“…Moreover, curative treatment with DM509 counteracted pre-established NASH in diet-induced obese mice with anti-inflammatory and remarkable antifibrotic effects widely exceeding OCA as standard of care (54). Experimental studies in UUO mice revealed that DM509 decreased renal fibrosis and injury (55). DM509 had anti-inflammatory actions with reductions in TGF- β , TNF α , IL-1 β , and IL-6 levels in the UUO mice (55).…”
Section: Progress With Multi-target Drugs For Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation